Managing the flow of scientific information for agricultural research in small countries: an issues paper - Ballantyne, Peter (International Service for National Agricultural Research The HagueNL, 1991)
Tries to identify mechanisms and strategies which can be used by agricultural research systems in small countries to gain access to relevant scientific information. Discusses the major issues and factors that influence the flow of scientific information in small countries and provides a framework for analysis by managers and information specialists.